A voice controlled smart home automation system using artificial intelligent and internet of things - Mohamed A. Torad; Belgacem Bouallegue; Abdelmoty M. Ahmed (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
The objective of this work is to take a step further in this direction by incorporating voice control and artificial intelligence (AI) into internet of things (IoT)-based smart home systems to create more efficient automated smart home systems. Accordingly, a home automation system proposal is presented, in which the related functions can be controlled by voice commands using an android or web application via a chat form. The user issues a voice command, which is deciphered by natural language processing (NLP). To accommodate the user’s request, the NLP classifies it into operation commands. Arduino and Raspberry Pi are used to translate the commands extracted from NLP into reality. Based on this, home applications can be controlled. Also, the utilities consumption could be calculated, saved, and paid on time. This is in addition to the introduction of a machine learning (ML)-based recommendation system for automated home appliance control. In this approach, the mobile or web application is considered as the central controller, deciding the appropriate actions to fulfill the user’s desires. The presented work has been put into practice and tested. It proved to be applicable, as well as having the potential for making home life more comfortable, economic, and safe.